Analisis Komparatif Strategi Tax Planning PPh Pasal 21 (TER) melalui Metode Net dan Gross Up sebagai Upaya Efisiensi Beban Pajak Penghasilan Badan pada CV. Bumi Pertiwi Makmur - Kiswatul Imama; Pujo Gunarso (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze tax planning strategies for Article 21 Income Tax (PPh Article 21) using the Average Effective Rate (AER/TER) by comparing the Gross method currently applied by the company with the Net and Gross-Up methods, in order to achieve efficiency in Corporate Income Tax expenses at CV Bumi Pertiwi Makmur. This research employs a quantitative descriptive method with a case study approach. The data used include employee income data, Article 21 Income Tax calculations, and the company’s income statement for the March 2024 period. The analytical technique applied is comparative analysis to assess differences in fiscal treatment and their impact on the Corporate Income Tax burden. The results indicate that the Net method gives rise to a positive fiscal correction because the Article 21 Income Tax borne by the company constitutes a non-deductible expense, thereby increasing taxable income. Meanwhile, the Gross-Up method provides a tax allowance that can be recognized as a deductible expense, resulting in no positive fiscal correction and enabling a reduction in the Corporate Income Tax burden. Quantitatively, the implementation of the Gross-Up method generates Corporate Income Tax savings of 1.001.451 compared to the Net and Gross methods. Therefore, the Gross-Up method is considered the most effective strategy for Article 21 Income Tax planning.